PENERAPAN BUDIDAYA FODDER JAGUNG DENGAN SISTEM PENYIRAMAN TIMER DIGITAL OTOMATIS SEBAGAI PAKAN KAMBING ETAWA DAN DOMBA PADA KELOMPOK TANI DI DESA BENUA RAJA ACEH TAMIANG - Novianda; Beni Al Fajar; Liza Fitria (LPPM dan PM Universitas Samudra, 2020)
Corn fodder as alternative feed to replace grass, it can be planted on small land, arranged in a shelf rack with a tray. Corn fodder can be harvested for a minimum of two weeks, and yields can be given directly to livestock. by being appointed or even can be rolled up so the tray will clean again. Corn fodder can be consumed as a whole until the root without remaining. The basic ingredient of making corn fodder is corn seeds. One kilogram of corn seeds can produce as much as three up to four kilograms of corn fodder. Planting corn fodder does not use soil, but needs enough water. Farmers must use an automatic digital timer to overcome water shortages so that watering can be done regularly by adjusting the time on the automatic digital timer. The watering time setting is set for seven sessions, with an interval of 2-4 hours. and the watering life time for 1 minute. in session one the appliance will turn on watering the corn fodder at 05.30 on 05.31 off. In session two at 07.30 on, 07.31 off. In session three at 09.30 on, 09.31 off. In session four at 11.30 on, 11.31 off. In session five at 4.00 pm. on, 4.30 pm. off. In session six at 6.00 pm. on, 18.01 off. In session seven at 20.00 on, 20.01 off. watering is arranged at the same time during each day starting from Monday – Sunday and the tool will turn on automatically for daily watering